Flowers of our lives. - Zielinska, Joanna; Bird, Daniel; Cichocki, Sebastian; Coron, Olivier; Kurylek, Dominik; Lubiak, Jaroslaw; Malgorzata Tatar, Ewa; Muzyczuk, Daniel; O'Rilley, Sally; Pindera, Agnieszka; Ptacek, Jiri; Sasybasili, Nermin; et al. (Torun : Centre of Contemporary Art Znaki Czasu Torun, 2008)
Alvaer, Jesper ; Ataman, Kutlug ; Borowczyk, Walerian ; Dawicki, Oskar ; Doroszuk, Wojtek ; Khoór, Lilla ; Potter, Will ; Kusmirowski, Robert ; Macuga, Goschka ; Mona Chisa, Anetta ; Tkácová, Lucia ; Skapski, Lukasz ; Turek, Janina ; Urbanowicz, Andrzej
biog. per kunstenaar, biog. auteurs p. 232-233
Exhibition. Flowers of our lives. Torun. Centre of Contemporary Art Znaki Czasu Torun. 14.6.2008- 31.10.2008
boek